Design ethnography in information systems - Baskerville, Richard; Myers, M. (Wiley-Blackwell Scientific Publications Ltd., 2015)
Until recently, most ethnographic research in information systems has been based on the traditional anthropological model of ethnography. In this traditional model of ethnography, one of the most important data-gathering techniques is participant observation. The ethnographer observes and participates but does not actively seek to change the situation. In recent years, however, a new type of ethnographic research has emerged - one that can be called design ethnography. Design ethnography is where the researcher goes beyond observation and actively engages with people in the field. Our view is that design ethnography has much potential for research in information systems. It is a new form of engaged scholarship that bridges the gap between ethnographic research and design science research.